Traditional and Innovative Teaching Methods In Teaching English Language: Exploring Effective Methods for Teaching English Language (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of this paper is to evaluate the traditionalmethods of teaching as well as multimedia teaching and to suggest other usefulteaching methods that can be attempted in imparting knowledge to the students.Basically teaching must include two major components sending and receivinginformation. Ultimately, a teacher tries his best to impart knowledge as the wayhe understood it. So, any communication methods that serve this purpose withoutdestroying the objective could be considered as innovative methods of teaching.The use of innovative methods in educational institutions has the potential notonly to improve education, but also to empower people, strengthen governanceand galvanize the effort to achieve the human development goal for the country